2020
DOI: 10.1177/0734282920903164
|View full text |Cite
|
Sign up to set email alerts
|

Parental Involvement as a Holistic Concept Using Rasch/Guttman Scenario Scales

Abstract: Parental involvement (PI) in the education of their children is an important factor which should be taken into account when assessing and predicting children’s school outcomes. However, PI encompasses numerous operationalizations from checking homework, to communication with school, to organizing cultural outings. This study describes a Rasch/Guttman scenario-based scale designed to provide a holistic approach to measuring the PI construct. The Parental Involvement SCenarios scale (PISC-9) was administered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Existing research has called attention to parental involvement's relevant role in children's schooling and success [8][9][10][11]. Parental involvement is a complex construct that has been defined in several ways (e.g., [9,10,12,13]).…”
Section: Parental Involvementmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing research has called attention to parental involvement's relevant role in children's schooling and success [8][9][10][11]. Parental involvement is a complex construct that has been defined in several ways (e.g., [9,10,12,13]).…”
Section: Parental Involvementmentioning
confidence: 99%
“…Existing research has called attention to parental involvement's relevant role in children's schooling and success [8][9][10][11]. Parental involvement is a complex construct that has been defined in several ways (e.g., [9,10,12,13]). Recently, Antipkina and Ludlow [10] proposed a holistic concept of parental involvement: a "continuum of parenting behaviours ranging from those representing lower levels of involvement to those representing higher levels of involvement" (p. 856).…”
Section: Parental Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Mosby's Medical Dictionary [ 1 ], these two constituent conditions may be composed of multiple elements (such as cohesion, resilience, and communication skills) [ 2 ]. Early family function research is mainly aimed at different difficult groups, which is mainly used to understand and prevent dysfunctional family function and implement appropriate treatment activities when needed [ 3 ]. Over the past few decades, researchers have also created various models to evaluate family function.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, students may accidentally assess websites that are not suitable for them or not educational (Bruni et al, 2015;Byeon & Hong, 2015). Therefore, parents' support for young learners is vital to ensure that the learning process occurs without any glitches (Mohring et al, 2020;Antipkina & Ludlow, 2020;Gugiu et al, 2019;Hoover-Dempsey et al, 2005;Hoover-Dempsey & Sandler, 1997). Furthermore, (Amber et al, 2020;Bozkurt, 2020) in their research found that parents need to inspire and guide the student during the online learning sessions so that students get the most out of the online learning mode.…”
Section: Relationship Between Online Learning and Parent's Supportmentioning
confidence: 99%